Diagnostic Value of Alcohol Dehydrogenase (ADH) Isoenzymes and Aldehyde Dehydrogenase (ALDH) Measurement in the Sera of Colorectal Cancer Patients - Jelski, Wojciech; Mroczko, Barbara; Szmitkowski, Maciej (Digestive diseases and sciences, 2010)
Background The activity of total alcohol dehydrogenase (ADH) and class I isoenzymes is significantly higher in colorectal cancer tissue than in healthy mucosa. The activity of these enzymes in cancer cells is probably reflected in the sera and could thus be helpful for diagnosing colorectal cancer. Aim The aim of this study was to investigate a potential role of ADH and aldehyde dehydrogenase (ALDH) as tumor markers for colorectal cancer. We defined diagnostic sensitivity, specificity, positive and negative predictive values, and receiver-operating characteristics (ROC) curve for tested enzymes. Methods Serum samples were taken from 182 patients with colorectal cancer before treatment and from 160 control subjects. Total ADH activity and class III and IV isoenzymes were measured by photometric, but ALDH activity and ADH I and II by the fluorometric method, with class-specific fluorogenic substrates. Results There was significant increase in the activity of ADH I isoenzyme and ADH total in the sera of colorectal cancer patients compared to the control. The diagnostic sensitivity for ADH I was 76%, specificity 82%, AND positive and negative predictive values were 85 and 74%, respectively. The sensitivity and specificity of ADH I increased with the stage of the carcinoma. The area under ROC curve for ADH I was 0.72. Conclusion The results suggest a potential role for ADH I as marker for colorectal cancer.